(untitled) (Medico Legal Update, 2020)
Assessment on incidence of prehypertension and its association with stress among students in nursing college, Kelambakkam, Kancheepuram District, Tamil Nadu. A study was carried out among 80 nursing students to assess the stress level. The objectives were to assess the incidence of prehypertension, assess the level of stress and association of pre-hypertension with stress of nursing students with their selected demographic variables. The review of literature was done and organised under various aspects on studies related to pre-hypertension, stress and prehypertension and its association with stress among students. The research approach used for the study was quantitative approach and the design selected was descriptive research design 80 samples were participated in the study by using the convenient sampling technique. Demographic variables were assessed by using the statistical measurement. The level of significance selected was p<0.05 level. The study showed that there is no significant association between level of stress and demographic variables like socio economic status (x2 = 7.302), types of diet, type of stay, height, weight, BMI, habbits and co-morbidity. But age shows statistically significant with level of stress and statistically significant of association between prehypertension and stress.